Quantity surveyors' perceptions towards future directions of quantity surveying practices in Malaysia - Siew, Sik Nguong, 1989- , author; Fadhlin Abdullah, supervisor; Syamsul Hendra Mahmud, supervisor; Fakulti Alam Bina; Fakulti Alam Bina (2012)
Project Paper (Sarjana Muda) - Universiti Teknologi Malaysia, 2012